Al-Ḥarakāt al-munāhaḍah li al-mashāyikh wa al-‘ulamā’ al-ḥumr fī Priangan: al-Ittiḥād al-akhḍar 1920-1949 namūdhajan - Iskandar, Mohammad (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
The Islamic designation such as kiai or red ulema was used by supporters of The Green Association (SH) aimed at the elite of Islam who were labelled as communist or People’s Union (SR) and Indonesian Communist Party (PKI) activists. Giving a “red” label to the ulema was an effort to criminalize SH’s kiai and religious scholars supporting Islamic Association (SI) and it was considered harmful to the government authority. SH’s collective actions have succeeded enough in preventing the spread of Communism in the Priangan’s aristocrat community. Those actions were also managed to remove the sympathizers of the SI from the body of government’s bureaucracy. Yet, SH’s attempts to criminalize kiai and religious scholars using “red” label has failed. Even followers of the crime victim’s kiai had been increased, including the organization such as Al-Ittihadiyatul Islamiyyah (AII). Started from 1930s, SH’s collective actions started to decline until they completely disappeared.DOI: 10.15408/sdi.v24i2.5019